1993
DOI: 10.1080/02678299308026454
|View full text |Cite
|
Sign up to set email alerts
|

The development of polar discotic metallomesogens Vanadyl 1,3-diketonate complexes

Abstract: The dependence of mesomorphism of 1,3-diketonate vanadium-oxo (vanadyl) complexes on the number of side chains was investigated. These complexes have a large dipole normal to the disc plane and are under investigation in an effort to generate discotic phases with polar order. Relatively complex phase behaviour is observed when the vanadyl 1,3-diketonate complexes are appended with four phenyl groups with two octyloxy or decyloxy side chains each for a total ofeight side chains. These complexities are most like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The small reflection angles at 2h between 5-17 ‡ should indicate the coexistence of unidentified crystal phase and columnar mesophase. 17 Therefore, the peaks at 56.5 and 66.6 ‡C in the DSC trace on the first heating scan are attributed to melting and clearing point, respectively.…”
Section: Mesomorphic Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The small reflection angles at 2h between 5-17 ‡ should indicate the coexistence of unidentified crystal phase and columnar mesophase. 17 Therefore, the peaks at 56.5 and 66.6 ‡C in the DSC trace on the first heating scan are attributed to melting and clearing point, respectively.…”
Section: Mesomorphic Propertiesmentioning
confidence: 98%
“…4, which is similar to some textures exhibited by columnar mesophases reported earlier. 17,18 The powder Xray diffraction (XD) pattern of 1 recorded at room temperature prior to heating is that of a typical crystalline phase. XD patterns measured at 60 ‡C on heating, 60 ‡C on cooling and subsequently at room temperature are similar and exhibit a sharp reflection at small angles corresponding to a d-value of 38.4 A ˚(100) and several reflections in the wide angle region, the most prominent one corresponding to 4.8 and 4.3 A ˚, as shown in Fig.…”
Section: Mesomorphic Propertiesmentioning
confidence: 99%
“…We note that other columnar phases based upon nondiscoid molecules have been reported to be stabilized by the organization of dipoles 2b,d We have also investigated analogous metal bis(β-diketonate) complexes 1 and 2 (type 1 and 2 systems, respectively) and find that although 1 displays well-behaved liquid crystallinity with good thermodynamic stability,2c 2 did not appear to be liquid crystalline . In this paper we describe complexes related to 2 wherein an extension of the mesogenic core and the addition of dipoles have been used to stabilize liquid crystallinity.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, for Ni(II)-containing LC polymers, no data concerning linear polymers ar available, while some cross-linked polymers have been reported by Hanabusa et al , As to Pd(II)-containing LC polymers, a few cases have been reported concerning liotropic polymers, side chain orthopalladate polysiloxanes, and one single example of linear polymer . Finally, notwithstanding the good magnetic properties of oxovanadium complexes (a magnetic moment at room temperature of the order of 1.6 μ B has been reported for salicyladiminate oxovanadium complexes) and the possibility, experimentally assessed for low-molecular-weight complexes, of building molecular structures compatible with the onset of liquid crystallinity, a single example of a liquid-crystal polymer containing coordinated oxovanadium groups has been reported by Serrano and co-workers …”
Section: Introductionmentioning
confidence: 99%